Measuring Asian hate: Discordant reporting of race-based hate incidents and unfair treatment and association with measures of wellbeing - Ponce, Ninez A.; Adia, Alexander C.; Banawa, Rachel A.; Tan, Sean; Sabado-Liwag, Melanie D. (Frontiers in Public Health, 2022)
Background During COVID-19, anti-Asian discrimination increased in attention. Hate and unfair treatment are related but do not completely overlap. We expect those who report a hate incident would also report race-based unfair treatment, yet feelings of social desirability or self-blame may lead to under-reporting of unfair treatment. Objectives To describe reporting of an experience of race-based hate but not an experience of race-based unfair treatment among Asians in California and explore the association between this reporting discordance with (1) serious psychological distress, (2) forgoing needed medical care, (3) increased household interpersonal conflict, and (4) feeling unsafe in their neighborhood. Methods We used the 2020 California Health Interview Survey's AANHPI COVID Module, conducted weighted descriptive and multivariate analyses, and computed adjusted relative risks (RR). The multivariate models controlled for Asian subgroup, age, gender, immigrant status, education level, poverty, and English proficiency. Results Among Asians who reported race-based hate (6.9% overall), 62.4% reported not experiencing race-based unfair treatment. Compared to Asians not reporting a hate incident, this “discordant” group was more likely to experience serious psychological distress (RR = 6.9), forgo necessary medical care (RR = 2.4), increased household interpersonal conflicts (RR = 2.7), and feel unsafe in their neighborhoods (RR = 3.0). The “concordant” group did not post significant effects for severe psychological distress nor forgoing necessary medical care. Discussion Most Asians reporting hate did not report race-based unfair treatment, and this group is most affected by the consequences of a hate incident. We indicate future directions for research and policy.